2005
DOI: 10.1002/ange.200501740
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anion‐Binding Properties, and In Vitro Anticancer Activity of Prodigiosin Analogues

Abstract: Doppelt wirksam: Das Erkennen des Chloridions und der H+/Cl−‐Ionentransport („symport“) durch die Membran könnten die biologische Wirkung von Prodigiosin gegen Tumoren erklären, wie aus Modellstudien unter Beteiligung pyrrolbasierter Anionenrezeptoren folgt, die als Mimetika der Schlüsselelemente dieses natürlichen Pigments entworfen wurden (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 23 publications
3
42
0
1
Order By: Relevance
“…The cis isomer ( 23 or 25b ) is believed to possess an optimal juxtaposition of functional groups for activities such as anion transport and cation binding. 77,78 An evolutionary advantage may therefore be conferred on bacteria that have evolved oxidative carbocyclization enzymes (e.g., RedG and McpG) that allow the C ring of prodigiosin and undecylprodigiosin to be functionalized at the carbon atom directly adjacent to the azafulvene core. Such functionalization generates significant 1,3-allylic strain in the trans isomer.…”
Section: Isolation and Structural Elucidationmentioning
confidence: 99%
“…The cis isomer ( 23 or 25b ) is believed to possess an optimal juxtaposition of functional groups for activities such as anion transport and cation binding. 77,78 An evolutionary advantage may therefore be conferred on bacteria that have evolved oxidative carbocyclization enzymes (e.g., RedG and McpG) that allow the C ring of prodigiosin and undecylprodigiosin to be functionalized at the carbon atom directly adjacent to the azafulvene core. Such functionalization generates significant 1,3-allylic strain in the trans isomer.…”
Section: Isolation and Structural Elucidationmentioning
confidence: 99%
“…However, several carrier systems have been reported that induce apoptosis. For instance, prodigiosin (a naturally occurring small-molecule-based ion transporter) and its analogues are known to induce cancer cell death by altering intracellular pH gradients through HCl transport 1618 . Recently, we found that a synthetic diamide-strapped calix[4]pyrrole 1 (Fig.…”
mentioning
confidence: 99%
“…Sessler and coworkers reported the NH hydrogen bonding-based complexation between the protonated dipyrrins 16 and 17 (Figure 9) and for chloride anion (added as a TBA salt). In CH 3 CN solution, association constants of 8.8 × 10 5 and 3.0 × 10 5 M −1 , respectively, were determined by isothermal titration calorimetry (ITC) [47]. Other examples of complexation of anionic zinc salts were published by Dolphin and coworkers [48].…”
Section: Dipyrrin- Dipyrrinone- and Dipyrromethane-based Anion Rementioning
confidence: 99%
“…In 2005, Sessler and coworkers reported the chloride transport properties of the synthetic prodigiosin 41 through vesicle membranes via a co-transport H + /Cl − mechanism [47]. An X-ray diffraction analysis of 41 revealed a chloride anion hydrogen bonded to three NH sites [47].…”
Section: Prodigiosin- Tambjamine- and Perenosin-based Anion Recepmentioning
confidence: 99%